Midgut volvulus after laparoscopic appendectomy - Macedo,Maurício (2012)
The authors report a case of a 13-year old child who was submitted to a laparoscopic appendectomy and developed, during the postoperative period, an intestinal obstruction caused by small bowel volvulus in the absence of a congenital malrotation.